A continuous flow-batch hybrid reactor for commodity chemical synthesis enabled by inline NMR and temperature monitoring. Issue 38 (20th September 2018) - Schotten, Christiane; Howard, Joseph L.; Jenkins, Robert L.; Codina, Anna; Browne, Duncan L.
Abstract: Inline, real time NMR and temperature measurements have been used to optimise the continuous flow synthesis of difluoromethyltrimethylsilane (TMSCF2 H) by the reduction of the Ruppert-Prakash reagent (TMSCF3 ). These measurements were used to maximise the space-time-yield, while ensuring this exothermic process remains safe. In this way, a three-fold increase in space-time-yield was achieved compared to the reported batch procedure, isolating 25 g of pure TMSCF2 H after 105 min. Graphical abstract: Image 1